O direito de votar dos imigrantes no Brasil: em defesa da capacidade eleitoral ativa - Medeiros, Bruna Agra de (2023)
Political representativeness in Brazil must consider that the exercise of citizenship precedes nationality. The flow of immigration in the country is significant, with the exception of the rates related to the health exceptionality of Covid-19 (Sars-coV-2). The Federal Constitution of 1988 prohibits the electoral enlistment of foreigners (art. 14, §2º) and suppresses the right to choose political representatives through voting unnaturalized immigrants who reside in the country. Considering that immigrants arriving in Brazil can establish residence on Brazilian soil, the study of the subject is a priority, since citizenship rights must be assured to all without distinction. Citizenship is based on the individual's sense of belonging to the community and, as such, must be exercised in an integral way and not conditioned by the bond of nationality in relation to the State. The aim is to study the reason for the constitutional deprivation of nonnaturalized people from exercising the political right to vote in Brazil, even though they may be holders of other political rights. The hypothesis is raised that it is possible to legally allow the exercise of the political right to vote at the national level. The hypothesis starts from the experience of supranational citizenship in the European Union and from the observation that, among the Member States and associates of Mercosur, only Brazil, Guyana and Suriname maintain the prohibition of active electoral capacity to non-naturalized immigrants and domiciled in their respective territories. Data on migration flows are presented (at the global, Latin American, Brazilian level and related to the complications caused by the coronavirus pandemic) and then international experiences of the European Union are discussed, as well as those of Mercosur countries to demonstrate how its constitutional and infraconstitutional norms deal with the theme. Citizenship and the need for such a concept to be improved are discussed, as well as its correlation with nationality and democracy. The perspective of cosmopolitan citizenship is exposed as a way to strengthen citizenship rights and make possible the concreteness of the human and political right of the active electoral capacity of these immigrants, and the legislative initiatives already admitted by the Brazilian Legislative Power on the subject are demonstrated. The objective is to show the indispensability of the right to vote for non-naturalized immigrants and the need to think about readjustment in the constitutional norm. The study is based on the application of the hypothetical-deductive method, with historical and comparative procedures. This is applied and practical research, whose approach is qualitative and supported by bibliographical sources, international documents, statistical data and academic works. Authors such as Immanuel Kant, Hannah Arendt, Benito Aláez Corral and T. H. Marshall are used. It is suggested the proposition of a new Constitutional Amendment Proposal (PEC) to Constitution as an adequate legal way to allow immigrants who have not naturalized Brazilians to vote in elections at the municipal, state and federal levels, or even enact one of the 4 PECs currently pending in the legislature. It is concluded that the current constitutional prohibition violates the democratic principle and impacts their reality because it silences them in relation to their political thoughts and desires and harms them in the face of the lack of political representation of community participation.